(untitled) (Scientific journal of the Fergana State University, 2024)
The article studies the soil and ecological conditions of the kholmadyrs from the point of view of the emergence and development of agricultural landscapes under the influence of irrigation in the adyrs of the Fergana Valley. The types of hilly agricultural landscapes of the Fergana Valley, their location and development features in the context of territories have been studied. It is based on the fact that changes in the landscape and ecological conditions of the adyrs of the Fergana Valley are directly related to the development of agricultural landscapes. For this reason, the main features of the emergence of agricultural landscapes were studied and measures for their placement were developed.